Peritoneal cavity and mesenteries (Henry Stewart Talks, 2025)
Peritoneal cavity structure and layers, Roles of parietal and visceral peritoneum, Mesenteries arrangement and function, Vascular and nerve supply in mesenteries, Clinical relevance in peritonitis and ascites, Importance in diagnosis and surgery